Fabrication and investigation of multi-layered preferentially aligned structures - Chua, Chalmers Jun Yang (Nanyang Technological University, 2023)
This study involves the investigation of the drying time of an individual colloidal system and the fabrication of multi-layered preferentially aligned structure with magnetised alumina platelets of 10030 and 02025. Alumina platelets of 10030 would refer to the size of dimensional size of the micro-platelets of 10 microns in diameter and 0.030 microns thickness and the Alumina platelets of 02025 would refer to the dimensional size of the micro-platelets of 2 microns and 0.025 microns thickness.